Checklist with a key to genera and subgenera of dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) present and supposed for Ecuador - Chamorro, William; Marín-Armijos, Diego; Granda, Valeria; Vaz-de-Mello, Fernando Z. (Revista Colombiana de Entomología, 2018)
The beetles of the Subfamily Scarabaeinae are a group that have been used in taxonomic, ecological, natural history, biodiversity and conservation studies recently, as they are good indicators of habitat quality and due to their great genera and species richness. Their taxonomy is relatively well known, however new taxa and nomenclatural changes are frequently ocurring, mainly due to taxonomic revisions at the genus level. Currently in the Neotropics, 127 taxa (between genera and subgenera) are recorded, with 59 taxa belonging to 33 genera and 220 species (with 23 new records) present in Ecuador, and nine more genera that allegedly could be registered. With the aim of promoting the study and knowledge of this group in Ecuador, an identification key for the genera and subgenera present and/or supposed to be present in this country is provided in this work, which includes current taxa with Scarabaeinae (Coleoptera: Scarabaeidae) for the neotropic.